OUTCOMES OF VITRECTOMY IN TERSON SYNDROME: A Multicenter Canadian Perspective. Issue 7 (July 2020) - Nazarali, Samir; Kherani, Irfan; Hurley, Bernard; Williams, Geoff; Fielden, Michael; Adatia, Feisal; Kherani, Amin
Abstract : Purpose: To characterize the presentation of Terson syndrome, the occurrence of a vitreous hemorrhage in association with intracranial hemorrhage, and report on the outcomes of vitrectomy at two major centers in Canada. Methods: Retrospective chart review of consecutive patients with Terson syndrome undergoing vitrectomy by retina specialists over the last 10 years. Primary outcome was the change in best-corrected visual acuity (BCVA) at 3 months from baseline. Secondary outcomes included the association between baseline BCVA and final BCVA, and the association between final BCVA and timing of surgery (early vs. later than 90 days). Results: A total of 14 eyes of 11 patients were included. The mean time between observation of intraocular hemorrhage and vitrectomy was 160 days. Baseline preoperative BCVA was logarithm of the minimum angle of resolution 1.57 ± 1.03 (Snellen 20/740), which improved to logarithm of the minimum angle of resolution 0.53 ± 0.82 (Snellen 20/70) at the final postoperative follow-up, P = 0.01. Baseline BCVA was not significantly correlated with final BCVA, Spearman's rho = 0.016, P = 0.957. Final BCVA did not significantly differ between those who had surgery before 90 days compared with after 90 days, P = 0.087. Conclusion: Vitrectomy is safe and effective and should be considered for nonclearing vitreal bleeding due to Terson syndrome. Ocular hemorrhaging in Terson syndrome can be observed conservatively for spontaneous improvement without the risk of reduced visual potential. Ophthalmic evaluation should be considered promptly after intracranial hemorrhage. Abstract : Retrospective chart review characterizing the presentation and surgical outcomes of Terson syndrome in patients presenting to two major ophthalmic centers in Canada over the last 10 years.